Research into judgments of scenario’s about corruption - Dormaels, Arne (2009)
Research into Judgment of Scenario’s about Corruption Studying a stealthy offence such as corruption means from a methodological point of view a challenge. Previous theoretical studies dealt in the first place with the question how to define corruption whereas a limited number of studies empirical addressed the question how the perception of corruption is conditioned. This came to our opinion at the expense of the conceptualisation of corruption respecting its various shades: what are the key elements that influence a person’s perception of corruption? To answer this question we will approach corruption in our research as a social construction that is a result of social interpretation or perception. The perception of corruption is not a linear judgement. Our assumption is that is one’s perception shifts along multiple dimensions in relation to the particular activity, the context of the observer and in relation to the act being observed. These perceptions can vary in time and across different social groups. The focus of our study is to more precisely elucidate these shifts in order to enhance our understanding of corruption. In other words we will try to catch these variables or combinations of variables which determine the perception of corruption in relation to the social group he belongs to. For that reason we will evolve Peters and Welch’s methodology and conduct a quantitative survey using a questionnaire composed of different scenarios. This research instrument will consist of a questionnaire composed of various scenarios illustrating “black-grey-white corruption”. In our presentation we will address relevant theoretical and methodological studies in respect of elaborating our survey instrument